A comparative biochemical study on the non diabetic obese and non obese subjects with cardiovascular disease - Naidu, M. Prasad; Prasad, S. V.; Reddy, B. Madhusudan; Rajasekar, Sujith Tumkur; Aruna, P. (International Journal of Research in Medical Sciences, 2017)
Cardiovascular disease is now a major public health problem in India and is emerging as a major killer. The non diabetic obese and non obese subjects with cardio vascular disease” were carried out with the objective of studying or investing the (effect) cause of cardiovascular diseases in obese and Non-obese subjects. The level of lipoprotein a of non obese subject showed a significant (P < 0.001) increase than in the obese subject. The level of lipid ratio (total cholesterol / HDL cholesterol) found to be significantly (P < 0.001) high in obese subjects than in non-obese subjects. The present study has been designed to evaluate or investigate the risk of cardiovascular disease due to obesity in both male and female middle age group.